2004
DOI: 10.1042/cs20030349
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and elimination of crystalloid fluid in pre-eclampsia

Abstract: Pre-eclampsia (PE) is a disease of pregnancy associated with peripheral oedema and hypovolaemia, but few details are known about how women with PE handle a volume load of crystalloid fluid compared with healthy pregnant women. To study this issue, Ringer's acetate solution (12.5 ml/kg of body weight) was given by intravenous infusion over 30 min to eight women with PE and to eight healthy pregnant women matched with respect to gestational week (mean, 34 weeks). Venous blood was sampled and excreted urine was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…The unknown parameters in the kinetic model were estimated individually for each experiment, using Matlab version 4.2 (Math Works Inc., Notich, MA), in which process a non-linear regression analysis was used to fit the solution to the differential equations given above to the data on dilution [9]. The validity of the used model has recently been discussed [5].…”
Section: Kinetic Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unknown parameters in the kinetic model were estimated individually for each experiment, using Matlab version 4.2 (Math Works Inc., Notich, MA), in which process a non-linear regression analysis was used to fit the solution to the differential equations given above to the data on dilution [9]. The validity of the used model has recently been discussed [5].…”
Section: Kinetic Calculationsmentioning
confidence: 99%
“…The Hb series was analyzed by volume kinetics, which is pharmacokinetics adapted to fluid infusions [3][4][5]. Volume kinetics implies that fluid infused at the rate k i expands a central body fluid space (v) which is reduced to its baseline size V by two dilution-dependent mechanisms; k r which eliminates fluid by urinary excretion, and k t which translocates fluid to a peripheral body fluid compartment.…”
Section: Kinetic Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the kinetics of crystalloid fluids seems to be affected by albuminuria, which indicates damage to the glycocalyces of the glomeruli. For example, minimal albuminuria increased the rate of elimination of crystalloid fluid infused just before major abdominal surgery [39] and preeclamptic women had twice the distribution and elimination rates of Ringer´s acetate when compared to matched pregnant controls [40].…”
Section: Future Viewsmentioning
confidence: 99%
“…Co-administration of different catecholamines has been demonstrated to induce different effects on the dynamics of volume expansion of crystalloid infusion (3,4). Research has also indicated that the particular illness in the patient may influence the dynamics of volume expansion (5). Additionally, different fluids present different fluid shift (6).…”
Section: Introductionmentioning
confidence: 99%